Removing the Barriers to Global Health Equity - MacDonald, Theodore H. (CRC Press, 2016)
Front Cover -- Contents -- Foreword by Amiya Kumar Bagchi -- Foreword by Ann Wylie -- Preface -- Acknowledgements -- List of relevant acronyms -- Dedication -- Chapter 1: Is neoliberalism compatible with global health equity? -- Chapter 2: Setting an optimum context for global control -- Chapter 3: Inequity in access to water -- Chapter 4: Neoliberalist approaches to healthcare and the transnational pharmaceutical corporations -- Chapter 5: The obstacle of war -- Chapter 6: A world mortgaged to war -- Chapter 7: Imperialism and global health